Photocatalytic efficiency of titania photocatalysts in saline waters - Albrbar Asma Juma; Bjelajac Anđelika; Đokić Veljko; Miladinović Jelena; Janaćković Đorđe; Petrović Rada (Journal of the Serbian Chemical Society, 2014)
The photocatalytic efficiency of the recently synthesized TiO2 powder, named P160, of the degradation of dye Dye C.I. Reactive orange 16 in natural and artificial seawater was investigated in comparison to its efficiency in deionized water and the efficiency of a standard TiO2 powder Degusa P25. It was shown that the photocatalytic efficiency of P160 was slightly higher than that of P25, probably due to slightly higher specific surface area, higher pore volume and larger pores of the powder P160. The efficiency of both photocatalysts in natural and artificial seawater was significantly lower than that in deionized water. The overall rate of dye degradation for both types of photocatalysts is litle higher in artificial seawater than in natural seawater, which shows the influence of organic compounds naturally present in seawater on the photocatalysts activity. A saturation Langmuir-type relationship between the initial degradation rate and the initial dye concentration indicates that the adsorption plays a role in the photocatalytic reaction. The photodegradation rate constant k, which represents the maximum reaction rate, has similar values for P25 and P160 in all types of water due to the similar properties of the photocatalysts. [Projekat Ministarstva nauke Republike Srbije, br III 45019]